COSATU - the workers voice. ANC - the workers' choice - Manik Design. (1994)
With portraits of Nelson Mandela and 24 leaders of COSATU-unions + on the backside the list of ANC candidates for the April 1994 National Assembly elections; produced by the Shopsteward, organ of COSATU.